Improving the retention of free fibers in raw cotton and the separation of cotton from the air (Texas Journal of Multidisciplinary Studies, 2022)
The article describes a research work on reducing the amount of free fiber coming out of a separator installed in the technological process of ginneries, and a device for determining the content of free fiber in raw cotton is proposed. To reduce the sticking of cotton to the surface of the separator mesh, trapezoidal guides mounted on the separator device and tested in the lengths of the guides 15 cm and 20 cm 40 cm were proposed and the results were obtained.